Application of the Athlete's Performance Passport for Doping Control: A Case Report - Iljukov, Sergei; Bermon, Stephane; Schumacher, Yorck O. (Frontiers in Physiology, 2018)
The efficient use of testing resources is a key issue in the fight against doping. The longitudinal tracking of sporting performances to identify unusual improvements possibly caused by doping, so-called “athlete performance passport” is a new concept to improve targeted anti-doping testing. In fact, unusual performances by an athlete would trigger a more thorough testing program. In the present case report, performance data is modelled using the critical power concept for a group of athletes based on their past performances. By these means, an athlete with unusual deviations from his predicted performances was identified. Subsequent target testing using blood testing and the athlete biological passport resulted in an anti-doping rule violation procedure and suspension of the athlete. This case demonstrates the feasibility of the “athlete performance passport” approach where athlete`s performance is tracked on longitudinal way and might serve as an example for the practical implementation of the method.